2023
DOI: 10.12890/2023_003626
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of incidentally diagnosed pulmonary inflammatory myofibroblastic tumour with dramatic response to crizotinib in a postpartum woman

Abstract: Introduction: Inflammatory myofibroblastic tumours are rare neoplasms which most commonly affect children and young adults. With an intermediate malignant potential, they are typically detected in the abdomen, lung, mediastinum, head and neck, gastrointestinal tract, and genitourinary tract. Case description: We describe the case of a 33-year-old postpartum woman incidentally diagnosed with a pulmonary inflammatory myofibroblastic tumour following complaints of poorly controlled hypertension a week after caesa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Of the 17 other reports of ROS1 fusion containing IMTs we identified, 10 had a TFG‐ROS1 fusion (Ambati et al., 2018 ; Antonescu et al., 2015 ; Carcamo et al., 2021 ; Ingley et al., 2021 ; Lovly et al., 2014 ; Mai et al., 2019 ; Sommer et al., 2024 ; Styczewska et al., 2021 ; Yorke et al., 2023 ), two had a YWHAE1‐ROS1 fusion (Lovly et al., 2014; Comandini et al., 2021 ), and the fusion partner was not reported in five (Antonescu et al., 2015 ; Vassal et al., 2016 ). Of 15 cases where demographic data were available, the patients ranged in age from 4 to 61 years.…”
Section: Discussionmentioning
confidence: 96%
“…Of the 17 other reports of ROS1 fusion containing IMTs we identified, 10 had a TFG‐ROS1 fusion (Ambati et al., 2018 ; Antonescu et al., 2015 ; Carcamo et al., 2021 ; Ingley et al., 2021 ; Lovly et al., 2014 ; Mai et al., 2019 ; Sommer et al., 2024 ; Styczewska et al., 2021 ; Yorke et al., 2023 ), two had a YWHAE1‐ROS1 fusion (Lovly et al., 2014; Comandini et al., 2021 ), and the fusion partner was not reported in five (Antonescu et al., 2015 ; Vassal et al., 2016 ). Of 15 cases where demographic data were available, the patients ranged in age from 4 to 61 years.…”
Section: Discussionmentioning
confidence: 96%
“…A case describing the simultaneous location of IMT lateral to the ascending aorta near the root and inside the atrial septum has been reported [ 18 ]. IMT may also occur in pregnant women, potentially leading to pregnancy complications and worsening symptoms after delivery [ 19 ]. In addition, there have been very rare cases of IMT within the spermatic cord in elderly men, as described in the literature [ 6 ].…”
Section: Introductionmentioning
confidence: 99%